Going multinational: What are the effects on home market performance? - Robert Jäckle (Deutsche Bundesbank, 2006)
A number of recent studies nd evidence for the existence of a persistent performance gap between multinational enterprises (MNE) and their domestic competitors. Therefore, the question arises whether successful rms become MNEs or whether going abroad improves home market performance. This paper investigates to what extent MNEs have superior performance characteristics, both prior to and after they have switched from national to multinational activities. In the rst case results are quite clear: Future multinationals outperform domestic rms. Since self-selection occurs, an endogenous treatment approach is necessary for comparing ex-post performance of rms. Using probit estimates of the decision to become a MNE, Heckman's (1978) treatment model is applied to account for potential endogeneity issues. The results suggest that after switching, both productivity and wage growth are higher for newly founded MNEs than for national rms. Employment growth is superior before switching but does not exhibit signi cantly higher ex-post growth rates. Moreover, capital intensities at multinationals evolve towards the use of capital.
Keywords: F10; D24; F23; F21; 330; Multinational enterprises; productivity; endogenous treatment; Unternehmen; Globalisierung; Multinationales Unternehmen; Produktivität; Vergleich; Schätzung; Deutschland